Moritz Graf von Dietrichstein - Weiss, David, 1775-1846 (engraver):::Creator::::::::::::; Wagner, Friedrich Erhard, 1759-1813 (artist):::Contributor:::::::::::: (Vienna; Cappi und Diabelli; Austria)
Portrait engraving of Moritz Joseph Johann, a German prince and director of the Imperial Library.